Evaluation of hepatoprotective effect of Waltheria indica against various NSAIDs-induced hepatic damage in rats - Amol Chandekar; Neeraj Upamanyu; Amber Vyas; Atul Tripathi; Surendra Agrawal; Deenanath Jhade (International Journal of Phytomedicine, 2017)
The objective of the present study was to evaluate methanolic extract of leaves of Waltheria indica linn. for hepatoprotective potency of the potent solvent extract. The hepatotoxicity was induced by diclofenac, carbon tetrachloride (CCl 4 ) and acetaminophen. In CCl 4 induced hepatotoxicity study, animals were divided into five groups (n=6). Methanolic extract of Waltheria indica (WIM) groups were injected in doses of 400 mg/kg and 600mg/kg body weight along with CCl 4 and Silymarin 100mg/kg was taken as standard drug. Similarly procedure was followed in diclofenac and acetaminophen induced hepatotoxicity. Blood samples and liver were collected and liver hisopathological studies were carried out. These histopathological analysis suggested that WIM extract have the ability to reduce the degree of hepatic fibrosis induced by various factors. And concluded that WIM extract has significant hepatoprotective activity thus this study scientifically support the theory to use of this plant in traditional medicine for the treatment of liver disorders.